SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN ASISTEN TERBAIK DENGAN METODE TOPSIS DAN WP - Elyza Gustri Wahyuni; Nadya Khairunnisa; Fadhillah Abriyani; Nurul Fatikah Muchlis; Maria Ulfa (Teknoin, 2017)
The selection of the best assistants is an important aspect of performance management as it produces useful information for assistant administration decisions. Assistant administrative decisions is the selection of practicum managers, the determination of the amount of salary, and other decisions. The selection of the best assistants is not only for assistant administration decisions, but also useful as self-introspection and motivating to improve assistant performance. This research aims to apply decision support system with Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Weighted Product (WP) method to a system that can perform task in choosing the best assistant. TOPSIS method is used for sub-criteria calculation and WP method for criteria calculation. Testing is done with Netbeans software and Java programming language. The criteria that become the best assistant assessment are discipline, attendance, and Assistant Performance Values (NKA). Each criteria has sub-criteria, that is for Discipline has a sub-criteria are tardiness and cash payment, for attendance has sub-criteria debriefing, meeting, and teaching, and for NKA has sub-criteria mastery of material, responses questions, ability to motivate, ability to manage time, and spirit assistant. Alternatives are selected from the laboratory assistants in the Integrated Laboratory of Informatics, are Yaya, Za, Syilvia, Kahfi, Oddy, and Ridwan. Testing is done by entering data assistant as much as six people. The system performs haveÂ  faster calculation process than the manual calculation by producing the best assistant recommendation, namely Yaya with a value of 0.19734.